The mediating effect of dispositional mindfulness on the association between UPPS-P impulsivity traits and gaming disorder among Asia-Pacific young adults - Anson Chui Yan Tang; Regina Lai-Tong Lee; Paul Hong Lee; Keiko Tanida; Shun Chan; Simon Ching Lam; Jennifer Nailes; Joy P. Malinit; Jose Ronilo G. Juangco; Qing Wang; Jason Ligot; Lorna Kwai Ping Suen (BMC Psychiatry, 2024)
Abstract Background Little evidence is available to verify the mediating effect of dispositional mindfulness on the association between gaming disorder and various impulsivity traits. The present study aimed to investigate the mediating effect of dispositional mindfulness on the association between the five UPPS-P impulsivity traits and the risk of gaming disorder among young adults. Methods It was an inter-regional cross-sectional study using online survey in Australia, Japan, The Philippines and China. Impulsivity measured by the UPPS-P Impulsive Behavior Scale–Short version; dispositional mindfulness measured by the Mindfulness Attention Awareness Scale; and the risk of gaming disorder measured by the Internet Gaming Disorder Scale were collected in the focal regions. Structural equation modeling was performed by SPSS AMOS version 26 to verify the study hypotheses. Bootstrapped 95% confidence interval was reported. Statistical significance was indicated by the p-value below 0.05. Results Among the 1,134 returned questionnaires, about 40% of them aged 18–20 years and 21–23 years, respectively. 53.8% were male. 40.7% had been playing digital and video games for over 10 years. The prevalence of gaming disorder was 4.32%. The model fitness indices reflected that the constructed model had an acceptable model fit (χ2(118) = 558.994, p < 0.001; χ2/df = 4.737; CFI = 0.924; TLI = 0.890; GFI = 0.948; RMSEA = 0.058; SRMR = 0.0487). Dispositional mindfulness fully mediated the effect of positive urgency and negative urgency on the risk of gaming disorder. The effect of lack of premeditation on the risk of gaming disorder was partially mediated by dispositional mindfulness. However, dispositional mindfulness did not mediate the effect of sensation seeking on the risk of gaming disorder. Conclusions The varied associations between dispositional mindfulness and the five impulsivity traits hints that improving some impulsive traits may increase dispositional mindfulness and so lower the risk of gaming disorder. Despite further studies are needed to verify the present findings, it sheds light on the need to apply interventions on gamers based on their impulsivity profile. Interventions targeting at emotion regulation and self-control such as mindfulness-based interventions seem to be effective to help gamers with dominant features of urgency and lack of premeditation only. Other interventions shall be considered for gamers with high sensation seeking tendency to enhance the effectiveness of gaming disorder prevention.